Relevansi Etika Politik Peter L. Berger bagi Pembangunan Pariwisata di Indonesia - Bernardus Badj (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2024)
This paper aims to discuss the relevance of the political ethics of Peter L. Berger's development to the development and development of tourism in Indonesia in general and NTT in particular in Labuan Bajo, West Manggarai. The development and development of tourism in Indonesia aims to increase the quality and quantity of tourism destinations and create a tourism industry capable of driving the national economy. This has been carried out properly according to its purpose. However, there are several tourism developments in NTT which in the end only give rise to domination, resource grabbing, marginalization, subordination, exploitation and violence in its various forms. Peter L. Berger through his book Pyramid of Sacrifice, suggests a moral dimension, namely the problem of costs that may exist in political policies. A politician must take into account the consequences of his actions for others, especially cost considerations, namely the calculus of pain and the calculus of meaning. It is interesting that tourism development also creates a new context for the work of the Catholic church's pastoral ministry. Therefore, the Catholic church is required to actively participate in directing tourism development in order to ensure that all people can access and enjoy prosperity and justice together. The method used in this paper is the method of literature and the contribution of this paper to the welfare of the nation and state in all dimensions of life.